Experimental study of gas–liquid two-phase operating characteristics and bubble evolution law of a semi-open mixed-flow pump. (15th March 2023) - Luo, Xingqi; Yan, Sina; Sun, Shuaihui; Feng, Jianjun; Xie, Hang; Zhang, Lefu; He, Denghui
Abstract: This work experimentally studied the influence of gas and liquid distribution on a semi-open mixed-flow pump performance. High speed photography technology was contributed to obtain the evolution law of bubbles in the impeller. The results show that the inlet gas volume fraction ( IGVF ) and liquid flow rate are the main factors affecting the performance of the pump. The pressurization capacity linearly decreases with the increase in IGVF when the liquid flow rate is close the best efficiency point. However, this factor suddenly drops when the IGVF reaches a certain critical value under the condition of a low liquid flow rate. The spatiotemporal evolution characteristics of the isolated bubbles and gas column in the segregated flow were investigated. In addition, the bubbles are evenly distributed, and the flow pattern is mainly bubbly flow (BF) or aggregated BF (ABF) in the impeller inlet area without blades. Under small liquid flow rate conditions, the bubbles tend to coalesce into larger-sized gas-pocket with an increase in IGVF . The tip leakage vortex increases the turbulence intensity of the flow field. The results show that the bubbles downstream of the tip leakage vortex in the impeller channels are more easily broken into smaller bubbles and form a BF or ABF. Highlights: The visualization experiment of mixed-flow gas-liquid two-phase pump is carried out. Relationship between external characteristics and bubble distribution is clarified. Gas-liquid two-phase flow patterns in the impeller of the mixed-flow pump are obtained. The evolution process of isolated bubbles passing through the tip clearance is found. The dynamic circulation process of air pocket in the impeller are clarified.